Piperidone Analogue of Curcumin-loaded HPβ-cyclodextrin liposomes as delivery system for human cancer therapy - Alhabardi, S; Aboussekhra, A.; Alshamsan, A; Alomrani, A (Journal of medical and pharmaceutical sciences, 2017)
Cancer is a broad term used to describe different types of tumors affecting various parts of the human body. The resistance to multiple therapeutic agents, toxicity to healthy tissues, and lack of effective therapies obligate scientists to keep looking for new agents. Curcumin (diferuloylmethane) is a natural product. It has been reported that curcumin has anti-inflammatory, anti-diabetic, and anti-cancer effects. However, clinical use of curcumin is limited due to its poor aqueous solubility. Recently, a curcumin analogue, 5-Bis (4-hydroxy-3-methoxybenzylidene)-N-methyl-4-piperidone of curcumin (PAC), was synthesized to overcome this limitation. This compound showed significantly higher anticancer activity on breast cancer cell lines and colon cancer cell lines as compared to native curcumin. However, aqueous solubility of this new chemical compound limited its use and application. Liposomes were found to be the most promising system to use to overcome aqueous solubility and delivery limitations. Liposomes are a self-assembly of phospholipid molecules. They are biodegradable, biocompatible, and nontoxic carrier systems. These features make liposomes an ideal carrier system for anticancer agents. In this study liposomes were utilized to overcome PAC limitations. This project was designed to develop liposomal delivery system for PAC for cancer treatment and evaluate the anti-cancer properties of this system. Liposomal PAC formulae were prepared by the film hydration method and were optimized by adding hydroxypropyl-beta-cyclodextrin (HPβCD) and characterized in term of particle size, entrapment efficiency, release profile and cytotoxic activity. Liposomes with an average size below 150 nm and zwitterionic charge were obtained. Indeed, no major differences were seen in particle size and surface charge. However, HPβCD inclusion gave satisfied incorporation capacity reaching 68.1%. In addition, HPβCD inclusion in the liposomes resulted in increased in vitro release rate compared to conventional liposomes. On colon cancer cells, Annexin V/PI- Flow Cytometery cytotoxicity results revealed that the PAC-loaded HPβ-cyclodextrin liposomes trigger apoptosis by 75% in response (10 µM), whereas it was only 43% in response to the same concentration of PAC conventional liposomes, which confirmed their potential anti-cancer activity. On breast cancer cells, Annexin V/PI- Flow Cytometery cytotoxicity results showed that while PAC conventional liposomes have only minor cytotoxic effect (22-25%), PAC-loaded HPβCD liposomes induced 53% and 70% apoptosis in response to 5 µM and 10 µM, respectively. The cytotoxicity of PAC-loaded HPβ-cyclodextrin liposomes was more pronounced than PAC conventional liposomes in both cells, suggesting the benefits of using HPβ-cyclodextrin. Therefore, PAC-loaded HPβ-cyclodextrin liposomes indicate significant potential as delivery vehicles for the treatment of cancers.